2000
DOI: 10.1111/j.1471-0528.2000.tb11678.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital chylothorax in siblings

Abstract: Case reportThe parents were of Tongan origin, unrelated and in good health. There was no history of familial or metabolic disease in either family. At the age of 26 years, the mother booked in her first pregnancy at eight weeks of gestation. She had an uneventful pregnancy until 33 weeks of gestational age when she developed polyhydramnios. An ultrasound scan revealed that the fetus was hydropic with bilateral pleural effusions and ascites. Fetal lung lengths were 34 mm and 42 mm which were within the normal r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
(17 reference statements)
0
7
0
Order By: Relevance
“…Neonates with chylothorax may present with massive lymph loss inducing critical loss of fluid, lymphocytes, protein, coagulation factors, and antibodies [4]. There is no standard regime for the treatment of neonatal chylothorax, but many medical therapies have been reported such as total parenteral nutrition, medium-chain triglycerides, pleurodesis, and surgical interventions such as the ligation of the thoracic duct [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonates with chylothorax may present with massive lymph loss inducing critical loss of fluid, lymphocytes, protein, coagulation factors, and antibodies [4]. There is no standard regime for the treatment of neonatal chylothorax, but many medical therapies have been reported such as total parenteral nutrition, medium-chain triglycerides, pleurodesis, and surgical interventions such as the ligation of the thoracic duct [1][2][3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
“…Chylothorax is an abnormal condition of lymphatic fluid collection in the pleural space and is caused by a variety of etiologies such as congenital abnormalities and postoperative complications. The diagnosis of chylothorax is usually established by a fluid analysis, including a triglyceride content ≥ 1.1 mmol/L and a total cell count of ≥ 1000 cells/mm 3 or ≥ 80% lymphocytes [1].…”
Section: Introductionmentioning
confidence: 99%
“…A male preponderance has been reported [2,28]. PL can be associated with chromosomal anomalies including Turner, Down and Phelan McDermid Syndrome [28,50,69]. Therefore a chromosomal disorder should be ruled out by array-CGH analysis on a high resolution platform (Table 1).…”
Section: Genetic Counselingmentioning
confidence: 96%
“…It has been observed that males are most commonly affected than females. Moreover; most of the cases involve the right side of the chest [3]. Chylothorax is usually induced spontaneously due to lymphatic malformations or may be caused during birth, due to a trauma in the thoracic duct following difficult labor [4].…”
Section: Introductionmentioning
confidence: 99%